Predicate encryption for multi‐inner‐products. Issue 3 (21st June 2012) - Sun, Dongdong; Boyd, Colin; Nieto, Juan Manuel Gonzalez
ABSTRACT Predicate encryption is a new primitive that supports flexible control over access to encrypted data. We study predicate encryption systems, evaluating a wide class of predicates. Our systems are more expressive than the existing attribute‐hiding systems in the sense that the proposed constructions support not only all existing predicate evaluations but also arbitrary conjunctions and disjunctions of comparison and subset queries. Toward our goal, we propose encryption schemes supporting multi‐inner‐product predicate and provide formal security analysis. We show how to apply the proposed schemes to achieve all those predicate evaluations. Copyright © 2012 John Wiley & Sons, Ltd.